2021
DOI: 10.1016/j.celrep.2021.108805
|View full text |Cite
|
Sign up to set email alerts
|

The BRCT domains of ECT2 have distinct functions during cytokinesis

Abstract: Highlights d BRCT0 and BRCT1 promote ECT2 activation during cytokinesis d BRCT2 limits ECT2 GEF activity during metaphase and anaphase d BRCT2 binding to the GEF domain and RACGAP1 facilitates a narrow RhoA zone formation d Polo-like kinase 1 (Plk1) phosphorylates BRCT0 and binds each BRCT domain

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 69 publications
0
24
0
Order By: Relevance
“…Ect2 encodes for ECT2 protein, a GEF of the Rho family of small GTPases, that controls cytokinesis during cell cycle, and cell polarity ( 30 ). Structural studies found that exon 4, which codes for part of the BRCT 0 domain of ECT2, contributes to GEF activation and interactions with proteins important for cell spreading ( 31 , 32 ) (Figure 3A ). RNA-seq revealed that exon 4 of Ect2 is more excluded in Rbfox2 -CKO hearts.…”
Section: Resultsmentioning
confidence: 99%
“…Ect2 encodes for ECT2 protein, a GEF of the Rho family of small GTPases, that controls cytokinesis during cell cycle, and cell polarity ( 30 ). Structural studies found that exon 4, which codes for part of the BRCT 0 domain of ECT2, contributes to GEF activation and interactions with proteins important for cell spreading ( 31 , 32 ) (Figure 3A ). RNA-seq revealed that exon 4 of Ect2 is more excluded in Rbfox2 -CKO hearts.…”
Section: Resultsmentioning
confidence: 99%
“…Centralspindlin is a heterotetrametric complex consisting of a dimer of kinesin-6 family member mitotic kinesin-like protein (Mklp1), and a dimer of Cyk4 (Pavicic-Kaltenbrunner et al, 2007). The centralspindlin helps in recruiting the conserved RhoA guanine nucleotide exchange factor (RhoGEF)-epithelial cell transforming sequence 2 (Ect2) to the spindle midzone (Yuce et al, 2005; Chalamalasetty et al, 2006; Kamijo et al, 2006; Su et al, 2011; Kotynkova et al, 2016; Gomez-Cavazos et al, 2020; Schneid et al, 2021). Ect2 is essential for RhoA activation and thus for cleavage furrow ingression and cytokinesis in animal cells (Miki et al, 1993; Prokopenko et al, 1999; Kimura et al, 2000; Su et al, 2011; reviewed in Basant and Glotzer, 2017; Pollard and O’Shaughnessy, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Ect2 is essential for RhoA activation and thus for cleavage furrow ingression and cytokinesis in animal cells (Miki et al, 1993; Prokopenko et al, 1999; Kimura et al, 2000; Su et al, 2011; reviewed in Basant and Glotzer, 2017; Pollard and O’Shaughnessy, 2019). Ect2 consists of BRCT (BRCA1-C-terminal) domains at the N-terminus, and RhoGEF, pleckstrin homology (PH), and poly-basic cluster (PBC) domains at the C-terminus (Chalamalasetty et al, 2006; Su et al, 2011; Kotynkova et al, 2016; Schneid et al, 2021; Figure 3A). Through BRCT domains, Ect2 interacts with Cyk4, and the PH and PBC domains are critical for its membrane localization (Burkard et al, 2007; Somers and Saint, 2003; Yuce et al, 2005; Wolfe et al, 2009; Su et al, 2011; Kotynkova et al, 2016; Gomez-Cavazos et al, 2020; Schneid et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, both Ect2 and RhoA show more variability and/or cause cytokinesis phenotypes when over-expressed (Chalamalasetty et al, 2006; Piekny & Glotzer, 2008; Yuce et al, 2005). TCA-fixation-based immunofluorescence microscopy is still used as one of the more reliable methods to visualize the enrichment of RhoA at the equatorial cortex (Koh et al, 2021; Schneid et al, 2021; Yonemura et al, 2004; Yuce et al, 2005), while Ect2 overexpression can lead to cytokinesis failure (Chalamalasetty et al, 2006). In addition, measurements can be confounded by the variability in expression between transfected cells, and endogenous probes enable more quantitative measurements (Husser et al, 2021).…”
Section: Introductionmentioning
confidence: 99%